Crystal structure of haloxon, C14H14Cl3O6P. Issue 4 (December 2022) - Kaduk, James A.; Gates-Rector, Stacy; Blanton, Thomas N.
Abstract : The crystal structure of haloxon has been solved and refined using synchrotron X-ray powder diffraction data, and optimized using density functional theory techniques. Haloxon crystallizes in space group P 21 / n (#14) with a = 19.60382(6), b = 10.05473(3), c = 8.73591(2) Å, β = 92.6617(2)°, V = 1720.088(11) Å 3, and Z = 4. The structure consists of discrete molecules. The mean planes of the fused ring systems are approximately 0–11 and 011. The rings form staggered stacks perpendicular to these planes. There are no traditional hydrogen bonds in the structure, but several C–H⋯O and C–H⋯Cl hydrogen bonds contribute to the crystal energy. The powder pattern has been submitted to ICDD for inclusion in the Powder Diffraction File™ (PDF®).